FACIES AND ROCK TYPE DISTRIBUTION ANALYSIS ON K-39 SANDSTONE RESERVOIR UPPER CIBULAKAN FORMATION IN KILO FIELD, NORTHWEST JAVA BASIN - Arachman, Fitrah
Kilo Field, which is located in Offshore North West Java, has been in production since 1974. The hydrocarbon production in this field mostly comes from the K-39 sandstone reservoir at a depth of 1170 m. The distribution of the K-39 sandstone reservoir is considered to be wide and has relatively homogeneous properties. However, the results of the latest development drilling in Kilo Field, namely the KA-8 well, and its well log interpretation show that there is hydrocarbon that has not been produced from the K-39 reservoir. Well production tests reaching 1100 barrels of oil per day with 5% watercut. Meanwhile, production data from the surrounding wells has shown quite high production water (watercut). This suggests that the K-39 sandstone reservoir has properties with high heterogeneity and the current reservoir property distribution cannot explain the performance of the KA-8 well. Geological understanding related to the heterogeneity of the K-39 reservoir is needed as a reference for further development plans for the Kilo field, such as infill well drilling and water injection program. Several stages of research were carried out to gain an understanding of the heterogeneity of this reservoir, both vertically and laterally. These stages include lithofacies analysis, facies association analysis, electrofacies analysis, and rock type identification, as well as its relationship to reservoir rock properties. The main data used consists of well data and core data. Facies analysis from sample core shows that there are six lithofacies in the K-39 sandstone reservoir in Kilo Field, namely massive claystone, bioturbated siltstone, lenticular siltstone, flaser sandstone, parallel-stucture or structurless sandstones, and calcareous sandstones. The six facies can be associated into four groups, namely embryonic, immature accretion, mature accretion, and abandonment based on the shelf ridge depositional stages. In the other hand, rock type are classified into six group based on the flow zone indicator (FZI) method which represents reservoir unit within certain property range, namely DRT-12, DRT-11, DRT-10, DRT-9, DRT-8 and DRT-7. The descanding number in rock type name suggest the decreaing reservoir quality, DRT-12 represents the best quality reservoir and DRT-7 represents the worst quality reservoir. The mature accretion facies association of shelf ridge is a reservoir unit with good quality. This facies correlates with rock type DRT-12 and DRT-11 that has porosity between 24% - 36% and permeability between 30-400 milidarcy. Refer to distribution modeling, this facies has a dominant North-South trend and is thinning to the South. The immature accretion facies association of shelf ridge is a reservoir unit with fair to poor quality. This facies correlates with rock type DRT-10 and DRT-9 that has porosity between 13% - 25% and permeability between 5 - 55 milidarcy. Meanwhile, abandonment facies association correlates with rock type DRT-8 that has poor reservoir properties. Rock type DRT-7 correlates with the embryonic facies association.